2023
DOI: 10.1108/ijoem-07-2020-0739
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corporate governance and cost of equity: evidence from the ISIS era in Iraq

Abstract: PurposeThe cost of equity (COE) and corporate governance structure are the most critical factors affecting competition among publicly held companies. Accordingly, the present paper aims to examine the relationship between corporate governance and the COE in the wake of the Islamic State of Iraq and Syria (ISIS) in Iraq.Design/methodology/approachOur statistical sample includes 34 companies listed on the Iraq Stock Exchange from 2012 to 2017. Board structure (i.e. board size, board independence, CEO tenure, boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Accordingly, OCM systematically overestimate the return on their projects, thus investing excessively in the presence of internal funds (since they are not disciplined by stock markets or constrained by corporate governance mechanisms (e.g. Salehi et al, 2023;Bui and Krajcs ak, 2023). This argument is consistent with Miglo and Brodziak (2019), in the sense that they analysed different scenarios regarding the efficiency of entrepreneurs' decisions.…”
Section: Overconfident Managermentioning
confidence: 68%
See 1 more Smart Citation
“…Accordingly, OCM systematically overestimate the return on their projects, thus investing excessively in the presence of internal funds (since they are not disciplined by stock markets or constrained by corporate governance mechanisms (e.g. Salehi et al, 2023;Bui and Krajcs ak, 2023). This argument is consistent with Miglo and Brodziak (2019), in the sense that they analysed different scenarios regarding the efficiency of entrepreneurs' decisions.…”
Section: Overconfident Managermentioning
confidence: 68%
“…Accordingly, OCM systematically overestimate the return on their projects, thus investing excessively in the presence of internal funds (since they are not disciplined by stock markets or constrained by corporate governance mechanisms (e.g. Salehi et al. , 2023; Bui and Krajcsák, 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…For example, some studies find that there is a positive impact of managerial ownership on FP (e.g., Ali et al, 2023;Puspitasari and Widiyaningsih, 2023;Wijayanto et al, 2022;Wu and Dong, 2020). Conversely, other studies reported a negative impact of managerial ownership on FP (e.g., Waseem et al, 2023;Salehi et al, 2022;Adamu and Haruna, 2020), and others show that managerial ownership had no impact on FP (e.g., Mevania et al, 2022;Imade and Okoye, 2020).…”
Section: Managerial Ownership and Fpmentioning
confidence: 89%
“…The Iraqi Securities Commission (ISC) is tasked with the oversight and management of the Iraqi stock market, with a focus on enforcing adherence to established accounting and auditing protocols as well as safeguarding the interests of investors. The founding of this entity has had a positive impact on promoting transparency and improving corporate governance standards across the nation [23].…”
Section: Iraqi Accounting and Auditing Conditionmentioning
confidence: 99%